PERLINDUNGAN HUKUM INVESTOR PASAR MODAL (CAPITAL MARKET) AKIBAT EMITEN PAILIT BERDASARKAN UU KEPAILITAN DAN UU PERSEROAN TERBATAS DI INDONESIA - Fikradin, Rahmansyah; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
: All levels are beginning to investigate the capital market as an alternative source of financing for the community's economy. As the most noteworthy government authority, it is essential to guarantee legitimate sureness to safeguard the interests of individuals. One option for investing is in capital markets like shares. Stock investment offers state-owned businesses, particularly those listed on the capital market, an alternative means of financing. However, investing in shares on the capital market carries risks, such as bankruptcy, in addition to the possibility of profit. From the perspective of bankruptcy law, the purpose of this article is to determine the legal consequences of a joint stock company's bankruptcy decision for capital market investors and the legal protection of capital market investors in the event of a joint stock company's bankruptcy. With the assistance of standard legitimate examination techniques and subjective lawful information examination, it very well may be presumed that the chapter 11 of a business entity influences financial backers' portion possession in the business entity, for example makes a gamble of misfortune to the business entity. business entity capital misfortune because of lock-in. because of posting on the stock trade. Taking preventative measures or filing a civil lawsuit in civil court, either through the OJK as an intermediary or personally as a shareholder, provides investors with legal protection in this circumstance.Keywords : Bankruptcy, listed company, Investor, Capital market, Porolio investment.